Home and Horticultural Pests—Bees and Wasps - Brooks, Leroy H. (My University, 1992)
This publication describes the types of bees and wasps and how to control them.
MF793_1992_03
Keywords: MF793; Insects; Home and Family; Health and Safety; MF